2016
DOI: 10.1097/mao.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond GDP

Abstract: Both cochlear implantation and deaf education are widely cost effective in Latin America. In the lower-middle income economy of Guatemala, implant cost may have a larger impact. GDP is less influential in the middle- and high-income economies included in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The cost-effectiveness of cochlear implants has been established in developed countries 71 and in some developing countries. 71,7477 These analyses have evaluated the lifetime costs of cochlear implants, including the costs of the device and of surgery and rehabilitation, versus the benefits, as determined on the basis of health-preference measures. Measures of cost-effectiveness have also been used to compare cochlear implants with other treatments, such as educational programs for deaf persons, and these assessments have shown that cochlear implants compare favorably with other treatments.…”
Section: Treatment Of Sensorineural Hearing Lossmentioning
confidence: 99%
“…The cost-effectiveness of cochlear implants has been established in developed countries 71 and in some developing countries. 71,7477 These analyses have evaluated the lifetime costs of cochlear implants, including the costs of the device and of surgery and rehabilitation, versus the benefits, as determined on the basis of health-preference measures. Measures of cost-effectiveness have also been used to compare cochlear implants with other treatments, such as educational programs for deaf persons, and these assessments have shown that cochlear implants compare favorably with other treatments.…”
Section: Treatment Of Sensorineural Hearing Lossmentioning
confidence: 99%
“…As the number of CI operations continues to rise, one must consider the burden of preoperative imaging. The cost of preoperative imaging creates a financial burden for healthcare systems, especially those with scarce resources and for patients (3)(4)(5)(6). In one study by Brown et al (7), the average cost of imaging per patient was $2,343 for CT, $3,624 for MRI, and $5,830 for both.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the majority of CI units are distributed in developed countries because affordability remains a prohibitive challenge to people who need such devices in developing or under-developed countries. However, developing countries have started to estimate its cost-effectiveness in terms of the socioeconomic impact of hearing loss because the condition affects individuals in ways that limit their lives by depriving them of opportunities to be properly educated [ 1 , 2 , 3 , 4 ]. This includes impaired speech and language development and poor academic achievement, resulting in increased drop-out rates in adolescence.…”
Section: Introductionmentioning
confidence: 99%